THE EFFECT OF CHAIN STORY IN WRITING NARRATIVE TEXT ON THE SECOND YEAR STUDENTS OF SMAN 5 PEKANBARU - Gamal, Annisa Hafizah; Aruan, Rumiri; Novitri, Novitri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This pre-experimental research aimed to find out whether there is a significant effect of chain story on the ability of the second year students of SMAN 5 Pekanbaru in writing narrative text. This research was conducted by using one-group pre-test post-test design. Class XI IPA 5 was chosen as the sample by using cluster random sampling. A paired samples t-test was conducted to compare the students’ writing score before and after the treatment and to analyze the hypotheses. The result showed that the t-test score was 17.148 while t-table score in significance level 5%, df= 34 was 2.032. Since t-test was higher than t-table, it can be concluded that alternative hypothesis (Ha) was accepted and null hypothesis (H0) was rejected. It can be further understood that chain story has a significant effect on the ability of the second year students of SMAN 5 Pekanbaru in writing narrative texts. Based on the research findings, it is suggested that chain story can be used by teachers in teaching writing narrative text.Key Words: Effect, Chain Story, Writing, Narrative Text